Investigating Kinaesthetic Image Schemas In The Construction Of The Self And The Other In Bush’s Discourse Of The War On Terror: A Critical Discourse Analysis - Naidu, Sivabala Naidu P Rajoo (2010)

(untitled)
This study investigates kinaesthetic image schemas (KIS) involved in the discursive construction of the self and other in 24 radio addresses pertaining to the War on Terror articulated by the former US President, George W. Bush. The speeches were investigated according to two broad divisions: the pre-war and post war corpuses, each consisting of 12 speeches.